Analisis Keberhasilan Pengelolaan Irigasi Kecil oleh Perkumpulan Petani Pemakai Air P3A - Syaputra, Cecep (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the factors that drive the success of small-scale irrigation management by the Water Users Farmers Association (P3A) in Bandep Village, North Barito Regency, Central Kalimantan. The study used a mixed methods approach by combining qualitative and quantitative data. The results show that the success of small-scale irrigation management is influenced by the availability of skilled local experts, the stability of water volume during the planting season, the active participation of farmers and P3A administrators in irrigation operation and maintenance, and financial support from member contributions and government assistance. A SWOT analysis places irrigation management in the diversification quadrant, indicating that internal strengths are able to suppress external threats. The conclusion of this study confirms that sustainable small-scale irrigation management requires strengthening human resource capacity, farmer participation, and consistent financial support to improve P3A performance and agricultural production resilience. Keywords: Water User Farmers (P3A), Small Irrigation Management.